Engineering Mechanics Learning Model Planning - Nurudin , Arif (Greenation International Journal of Engineering Science, 2023)
Engineering Mechanics is a branch of the branch of mechanics with the stem of physics. The ability of students in the Engineering Mechanics course is low on average, so various learning models are needed to improve students' ability to achieve their competency standards. This research was conducted to make a plan for the learning model of Engineering mechanics at the Faculty of Engineering, University of Muhammadiyah Cirebon, which was based on the results of research in various educational institutions with various learning models, the purpose of this research is so that students can follow the Engineering mechanics course comfortably and enjoyably. The method used in this study is a literature review from various sources. The results showed that planning the learning model of Engineering mechanics needs to involve sharing dimensions of human life, not limited to cognitive, affective, and psychomotor, but also cooperation, collaboration, the friendship between friends, play, and the active role of lecturers to unite in student activities to do assignments both in groups and individually. Several models can be applied together including NHT, HOTS, STAD, Expository, innovative learning, social relations, and pair-check models.